Every day life of elderly with venous insufficiency, who use elastic compression socks (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objective: To comprehend every day of older people with venous insuffi ciency, who use elastic compression socks. Methods: Phenomenological research that interviewed 13 elderly attended Basic Health Units in the state of Minas Gerais, between November 2017 to January 2018. The depositions were organized in categories and discussed according to the Alfred Schütz social phenomenology and theme literature. Results: Emerged from the interviews that make explicit the perspective of the participants regarding their everyday activities with compression elastic socks: “main symptoms of the venous insufficiency relieved”, “adversities that permeate the use of elastic compression socks” and “long term use of compression elastic socks”. Conclusion: For elderly people with chronic venous insufficiency, the use of elastic compression socks promotes relieve of the symptoms; however, it demands help to put them on and take them off and provokes heat sensation and discomfort in the limbs. The elderly showed the expectation to continue the long term use of the elastic sock aiming at avoiding the relapse of varicose ulcers. To validate the adversities related to the use of this compression device may help the elderly to broaden their autonomy and functional capacity, which may be compromised by venous insufficiency.